Lateral forces in the filament lattice of vertebrate striated muscle in the rigor state. - Millman, B M (1983)
The repulsive pressure between filaments in the lattice of skinned rabbit and frog striated muscle in rigor has been measured as a function of interfilament spacing, using the osmotic pressure generated by solutions of large, uncharged polymeric molecules (dextran and polyvinylpyrrolidone). The pressure/spacing measurements have been compared with theoretically derived curves for electrostatic pressure. In both muscles, the major part of the experimental curves (100-2,000 torr) lies in the same region as the electrostatic pressure curves, providing that a thick filament charge diameter of approximately 30 nm in rabbit and approximately 26 nm in frog is assumed. In chemically skinned or glycerol-extracted rabbit muscle the fit is good; in chemically skinned frog sartorius and semitendinosus muscle the fit is poor, particularly at lower pressures where a greater spacing is observed than expected on theoretical grounds. The charge diameter is much larger than the generally accepted value for thick filament backbone diameter. This may be because electron microscope results have underestimated the amount of filament shrinkage during sample preparation, or because most of the filament charge is located at some distance from the backbone surface, e.g., on HMM-S2. Decreasing the ionic strength of the external solution, changing the pH, and varying the sarcomere length all give pressure/spacing changes similar to those expected from electrostatic pressure calculations. We conclude that over most of the external pressure range studied, repulsive pressure in the lattice is predominantly electrostatic.